1999
DOI: 10.1016/s0014-5793(99)01594-x
|View full text |Cite
|
Sign up to set email alerts
|

LDL binds to surface‐expressed human T‐cadherin in transfected HEK293 cells and influences homophilic adhesive interactions

Abstract: T-cadherin (T-cad) is an unusual glycosylphosphatidylinositol-anchored member of the cadherin family of cell adhesion molecules. Binding of low density lipoproteins (LDLs) to T-cad can be demonstrated on Western blots of smooth muscle cell lysates, membranes and purified proteins. Using HEK293 cells transfected with human T-cad cDNA (T-cad+), we have investigated the adhesion properties of expressed mature and precursor proteins and examined the postulate that LDL represents a physiologically relevant ligand f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…In contrast to the classical cadherins (45,49), T-cadherin is not concentrated in regions of cell-cell contact (1), but it can induce calcium-dependent homophilic aggregation in CHO cells (69) and in HEK293 cells (54). Under standard in vitro culture conditions, T-cadherin-transfected C6 cells did not exhibit increased cell-cell interactions compared with vectortransfected C6 cells (data not shown).…”
Section: T-cadherin Overexpression Results In C6 Cell Growth Suppressmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to the classical cadherins (45,49), T-cadherin is not concentrated in regions of cell-cell contact (1), but it can induce calcium-dependent homophilic aggregation in CHO cells (69) and in HEK293 cells (54). Under standard in vitro culture conditions, T-cadherin-transfected C6 cells did not exhibit increased cell-cell interactions compared with vectortransfected C6 cells (data not shown).…”
Section: T-cadherin Overexpression Results In C6 Cell Growth Suppressmentioning
confidence: 95%
“…We first noted that T-cadherin expression was increased in malignant astrocytoma cells from B8 mice compared with postnatal day 2 normal cultured astrocytes or nonneoplastic B8 astrocytes (28). Several T-cadherin molecular species were noted (50,(53)(54), ranging from 95 to 130 kDa. Since the active form of the molecule is 105 kDa, it was unclear from these studies whether this increase in T-cadherin expression was associated with astrocyte tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Since T-cadherin has been shown to bind low density lipoprotein (LDL) cholesterol [Resink et al, 1999], we next analyzed the association between rs12051272 genotypes and the levels of LDL cholesterol using the data from whole Suita study participants. The rs12051272 genotypes showed no significant association with serum LDL cholesterol levels (P = 0.19), as well as with total or HDL cholesterol levels (P = 0.46 and 0.16, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid sequencing of tryptic fragments of protein purified from human aortic medial tissue and immunoblot analysis of purified proteins indicated that p105 is identical with mature human T-cad (12) and that p130 is identical with the unprocessed T-cad precursor (11). In HEK293 cells stably transfected with human T-cad cDNA a colocalization of LDL-binding and anti-T-cad immunoreactivity to the expected mature (105 kDa) and precursor (130 kDa) forms of T-cad was shown (18). Additionally, intact T-cad transfected cells exhibited a significantly increased specific cell surface binding of [ 125 I]-LDL that was sensitive to phosphatidylinositolspecific phospholipase C pre-treatment of cells (18).…”
mentioning
confidence: 95%